Testosterone complex and non-steroidal ligands of human aromatase. Issue 181 (July 2018) - Ghosh, Debashis; Egbuta, Chinaza; Lo, Jessica
Graphical abstract: Highlights: First crystal structure of testosterone complex of human aromatase is reported. Heme proximal region has a large surface cavity where polyethylene glycol binds. Polyethylene glycol exhibits weak inhibition of aromatase activity. The proximal cavity could serve as the site of interaction with other molecules. The data also reveals a water channel from the active site to the lipid interface. Abstract: Cytochrome P450 aromatase (AROM) catalyzes the biosynthesis of estrogen from androgen. Previously crystal structures of human AROM in complex with the substrate androstenedione, and inhibitors exemestane, as well as the newly designed steroidal compounds, have been reported. Here we report the first crystal structure of testosterone complex of human placental AROM. Testosterone binds at the androgen-specific heme distal pocket. The polar and hydrophobic interactions with the surrounding residues resemble the interactions observed for other ligands. The heme proximal region comprises the intermolecular interface in AROM, and also the putative interaction surface of its redox partner cytochrome P450 reductase. Unreported previously, the proximal region is characterized by a large surface cavity, unlike most known P450's. Using five best X-ray data sets from androstenedione and testosterone complexes of AROM, we now unequivocally show the presence of an unexplained ligand electron density inside the proximal cavity. The density is interpreted as ordered five ethylene glycol units of polyethylene glycols used as a solvent for steroids and also in crystallization. Interestingly, polyethylene glycol exhibits weak inhibition of AROM enzyme activity in a time dependent manner. Besides its critical role in the redox partner coupling and electron transfer process, the proximal cavity possibly serves as the interaction site for other molecules that may have regulatory effects on AROM activity. In addition, the new data also reveal a previously unidentified water channel linking the active site to the lipid interface. The channel could be the predicted passage for water molecules involved in catalysis.